O lugar dos provérbios no ensino de língua portuguesa: uma análise do livro didático de português do Ensino Fundamental II - Ana Paula Goncalves Santos (2013)
This qualitative research aims to analyze the work with proverbs in the collection Português: uma proposta para o letramento. The analysis, was done from the perspective of lexical competence, considered aspects such as lexical choice, the semantic value of proverbs from the degree of connotation, the concept of proverb and the differences between the proverb and other phraseological expressions. Considerations were presented on Lexicology and Phraseology, from which we show the fields of study of the lexicon as well as the main features of phraseological units, mainly of proverbs. Questions about the teaching of Portuguese were also essential for this work, since the study of proverbs, as part of the lexicon as well as linguistic resource of great persuasive power, is a n important aspect to be worked into the classroom. Despite the presence of these statements in various speeches and any change in the conception of language, brought by the linguistic sciences in the late twentieth century, and its contributions to education, proverbs are still outside the teaching of the Portuguese language. It is evident from this research, the strong presence of proverbs in different genres of texts in circulation, such as music, advertising, comics and literary texts, which reinforces the idea of the importance of working proverbs classroom.